Efavirenz does not meaningfully affect the single dose pharmacokinetics of 1200 mg raltegravir. (14th November 2016) - Krishna, Rajesh; East, Lilly; Larson, Patrick; Siringhaus, Tara; Herpok, Lisa; Bethel‐Brown, Crystal; Manthos, Helen; Brejda, John; Gartner, Michael
Abstract: Raltegravir is a human immunodeficiency virus (HIV)‐1 integrase strand transfer inhibitor currently marketed at a dose of 400 mg twice daily (BID). Raltegravir for once daily regimen (QD) at a dose of 1200 mg (2 x 600 mg) is under development and offers a new treatment option for HIV‐1 infected treatment‐naive subjects. Since raltegravir is eliminated mainly by metabolism via an UDP‐glucuronosyltransferase (UGT) 1 A1‐mediated glucuronidation pathway, co‐administration of UGT1A1 inducers may alter plasma levels of raltegravir. Efavirenz, an UGT1A1 inducer, was used to assess the impact of altered UGT activity on a 1200 mg QD dose of raltegravir. An open label, randomized, 2‐period fixed‐sequence Phase 1 study was performed in adult healthy male and female subjects (non‐childbearing potential) ≥ 19 and ≤55 years of age, with a body mass index (BMI) ≥ 18.5 and ≤32.0 kg/m 2 . Subjects ( n  = 21) received a single oral dose of 1200 mg raltegravir at bedtime on an empty stomach on Day 1 in Period 1. After a washout period of at least 7 days, subjects received oral doses of 600 mg efavirenz QD at bedtime for 14 consecutive days in Period 2. Subjects received a single oral dose of 1200 mg raltegravir co‐administered with 600 mg efavirenz on Day 12 of Period 2. Pharmacokinetic (PK) samples were collected for 72 hours following raltegravir dosing and analyzed using a validated bioanalytical method to quantify raltegravir plasma concentrations. PK parameters were estimated using non‐compartmental analysis. Administration of single 1200 mg oral doses of raltegravir alone and co‐administered with multiple oral doses of efavirenz were generally well tolerated in healthy subjects. Co‐administration with efavirenz yielded geometric mean ratios (GMRs) and their associated 90% confidence intervals (90% CIs) for raltegravir AUC0‐∞, Cmax, and C24 of 0.86 (0.73, 1.01), 0.91 (0.70, 1.17), and 0.94 (0.76, 1.17), respectively. The results show that efavirenz modestly reduced the exposure of raltegravir. The reduction in raltegravir exposure is not considered clinically meaningful. Copyright © 2016 John Wiley & Sons, Ltd.